Phenotype Evaluation and Estimation of Genetic Parameter of Baby Corn From Two Generation Selfing and Sibbing - Nailan Nabila; Yudiwanti Wahyu (Gontor Agrotech Science Journal, 2023)
Baby corn is consumed widely in Indonesia, but special corn varieties for baby corn production are not available until now. The objectives of this study were to evaluate phenotypes, estimate the genetic parameters from two generations of selfing and sibbing, and identify the genotypes to develop as baby corn variety. This study was conducted using a completely randomized block design with three replications. Genetic materials used consist of 19 genotypes. They were four genotypes S0, HS1, S1, S2 and three genotypes of HS2. Progenitors(S0) were Laksmi, Golden, Hawaii, and Baruna belonging sweet corn type. Baby corn’s phenotypes from two generations sibbing were more vigor than selfing. Families of HS2 dan S2 have a higher percentage of class A marketable cobs than generations before. Two generations sibbing and selfing increased genetic variances and broad-sense heritability. Families of HS2 had better phenotypic performance than S2, the percentage of class A marketable cobs was higher than S0 and HS1, number of cobs per plant was the highest broad-sense heritability estimation. HS2 families were considered to develop as open-pollinated baby corn varieties.